Ophiopogon muongnhensis (Asparagaceae, Convallarioideae), a new species from northwest Vietnam - Pham, van The; Tanaka, Noriyuki; Averyanov, Leonid V.; Maisak, Tatiana V.; Tran, Huy Thai; Nguyen, Huu Cuong; Nguyen, Khang Sinh (Phytotaxa, 2023)
Ophiopogon muongnhensis, a new species from Dien Bien Province, NW Vietnam, is described and illustrated. In having slenderly petioled clavate leaves it is most similar to O. griffithii originally described from NE India, but clearly distinguishable mainly by its wider (1.8–2.9 vs. 0.3–1.9 cm) leaf blades, wider (3.5–7.5 vs. 2–2.8 mm), obliquely (vs. explanately) expanded perianth lobes, and free narrowly deltoid (vs. laterally connate, linear-lanceolate) anthers. Notes on the habitat, conservation status, phenology, and taxonomic relationships with congeners were also provided.